2014
DOI: 10.1158/1538-7445.am2014-1992
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1992: Y-box protein-associated acidic protein promotes breast cancer progression and is a potential molecular target

Abstract: The Y-Box protein- associated acidic protein (YBAP1), also known as Complement component 1, q subcomponent binding protein, is a multifunctional protein which is involved in in the regulation of complement activation, pre-mRNA splicing and mitochondrial function. As YBAP1 has been implicated in tumorigenesis, this study evaluates its role in breast cancer metastasis. YBAP1 mRNA expression was analysed by quantitative real time RT-PCR and YBAP1 protein by Western blot, immunocytochemical and immunofluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 0 publications
0
17
0
1
Order By: Relevance
“…3 Meanwhile, the use of chemotherapy, radiotherapy, and hormone therapy significantly improved survival rate. 4 In recent years, our understanding of metastatic breast cancer has made great progress; however, metastasis is still the main cause of breast cancer morbidity and mortality, 5 and there is no satisfactory treatment for metastatic breast cancer. Therefore, defining metastasis-specific regulators makes it possible to classify, inform, and improve treatment options of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 Meanwhile, the use of chemotherapy, radiotherapy, and hormone therapy significantly improved survival rate. 4 In recent years, our understanding of metastatic breast cancer has made great progress; however, metastasis is still the main cause of breast cancer morbidity and mortality, 5 and there is no satisfactory treatment for metastatic breast cancer. Therefore, defining metastasis-specific regulators makes it possible to classify, inform, and improve treatment options of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that many types of cancer frequently metastasise towards specific target organs within the body. For example, breast cancer metastasises towards the brain, liver, lung and bone [115][116][117], colorectal cancer towards the liver and lungs [118] and lung cancer to the brain, bone, liver, lymph nodes and adrenal glands [115,119,120]. There have been advances towards creating MPS which can integrate multiple tissue microenvironments representative of different organ sites, with tissue-specific functions, these designs are often referred to as organs-on-chips [21].…”
Section: Organ-specific Metastasismentioning
confidence: 99%
“…In particular, a heterogeneous subpopulation of both proliferative and nonproliferative disseminated tumor cells (DTCs) survive the metastatic cascade through sustained tumor homeostasis or entrance into a period of long-term quiescence or dormancy, where dormant micrometastases or single cells often are observed in bone marrow (BM) aspirates yet remain challenging to detect with noninvasive screening (5,7). Late recurrence (after 5 or more years) has been observed predominately with estrogen receptor-positive (ER + ) breast cancer primary tumors, with more than 50% of late recurrences happening in the bone clinically (8)(9)(10). These late recurrences are thought to arise from dormant DTCs that survived as single cells or micrometastases and over time are stimulated by local cell-microenvironment interactions to reactivate and recommence growth (11,12).…”
Section: Introductionmentioning
confidence: 99%